2020
DOI: 10.1038/s41541-020-0168-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of mice with chimeric antigens displaying selected epitopes confers protection against intestinal colonization and renal damage caused by Shiga toxin-producing Escherichia coli

Abstract: Shiga toxin-producing Escherichia coli (STEC) cause diarrhea and dysentery, which may progress to hemolytic uremic syndrome (HUS). Vaccination has been proposed as a preventive approach against STEC infection; however, there is no vaccine for humans and those used in animals reduce but do not eliminate the intestinal colonization of STEC. The OmpT, Cah and Hes proteins are widely distributed among clinical STEC strains and are recognized by serum IgG and IgA in patients with HUS. Here, we develop a vaccine for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…This oral challenge model with the monitoring of faecal shedding and gastrointestinal colonisation represents a safe and useful VTEC colonisation model in the absence of BLS3 animal facilities. Murine VTEC colonisation models are cost-effective models that are feasible for large sample sizes and have been used previously for VTEC vaccine testing [ 29 , 69 , 70 ], but they have limitations, as they are not naturally colonised by VTEC strains and thus do not develop symptoms [ 16 , 32 ]. Consequently, persistent levels of colonisation are not maintained after 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…This oral challenge model with the monitoring of faecal shedding and gastrointestinal colonisation represents a safe and useful VTEC colonisation model in the absence of BLS3 animal facilities. Murine VTEC colonisation models are cost-effective models that are feasible for large sample sizes and have been used previously for VTEC vaccine testing [ 29 , 69 , 70 ], but they have limitations, as they are not naturally colonised by VTEC strains and thus do not develop symptoms [ 16 , 32 ]. Consequently, persistent levels of colonisation are not maintained after 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to correlate the protection achieved with high levels of H. pylori-specific IgG (Figure 6b). Some studies revealed that IgG antibodies lead to the elimination of the Shiga toxin-producing Escherichia coli, virulent Citrobacter rodentium, and rotavirus in the murine intestine [32,48,49]. The vaccines against H. pylori were also vaccinated by systemic immune routes such as intramuscular immunisation [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The engineered immunogens could present one or more key epitopes or immunogenic domains to induce epitope-specific antibodies or generate a broadly reactive antibody response. In recent studies, Roundleaf bat HBV core antigen, calcium-binding antigen 43 homologue (Cah), and H. pylori ferritin were respectively selected as the scaffold proteins for displaying key epitopes or immunogenic domains of pathogens including hepatitis B virus, Shiga toxin-producing Escherichia coli (E. coli) and Borrelia burgdorferi [31][32][33]. The structure-based engineered immunogen has higher structural stability and more reasonable epitope exposure compared to epitope-tandem immunogens, which means that it could generate a broader and more persistent antibody response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these conventional antigens, there is growing interest in exploring alternative vaccine approaches that target non-LEEencoded antigens. For instance, the subunit B of the Shiga toxin 2 (Stx2B), and outer membrane proteins such as LomW, OmpT, Cah and Hes have gained attention as potential antigens for vaccine development (20,22,(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…One promising strategy is the use of chimeric proteins that carry selected epitopes from various strains or pathogens. This approach has shown the potential to enhance the immunogenicity of the recombinant antigen and the possibility of eliciting a broader immune response ( 28 , 32 , 39 ).…”
Section: Introductionmentioning
confidence: 99%